Climate policies after Paris: Pledge, trade and recycle. Insights from the 36th Energy Modeling Forum Study (EMF36) - Christoph Böhringer; Sonja Peterson; Thomas F. Rutherford; Jan Schneider; Malte Winkler (University of Oldenburg, Department of Economics, 2021)
This article summarizes insights from the 36th Energy Modeling Forum study (EMF36) on the magnitude and distribution of economic adjustment costs of greenhouse gas emission reduction targets. Under the Paris Agreement, countries have committed to emission reduction targets - so-called Nationally Determined Contributions (NDCs) - in order to combat global warming. The study suggests that aligning NDCs with the commonly agreed 2°C temperature target will induce global economic costs of roughly 1% in 2030. However, these costs are unevenly distributed across regions. Countries exporting fossil fuels are most adversely affected from the transition towards a low-carbon economy. In order to reduce adjustment costs at the global and regional level, comprehensive emissions trading which exploits least-cost abatement options is strongly desirable to avoid contentious normative debates on equitable burden sharing. Lump-sum recycling of revenues from emissions pricing, in equal amounts to every household, appeals as an attractive strategy to mitigate regressive effects and thereby improving the social acceptability of stringent climate policy.
Keywords: D58; H23; Q54; Q58; 330; Paris Agreement; emissions pricing and trading; revenue recycling